Intramuscular fiber conduction velocity, isometric force and explosive performance. - Methenitis, Spyridon; Terzis, Gerasimos; Zaras, Nikolaos; Stasinaki, Angeliki-Nikoletta; Karandreas, Nikolaos (J Hum Kinet, 2016)
Conduction of electrical signals along the surface of muscle fibers is acknowledged as an essential neuromuscular component which is linked with muscle force production. However, it remains unclear whether muscle fiber conduction velocity (MFCV) is also linked with explosive performance. The aim of the present study was to investigate the relationship between vastus lateralis MFCV and countermovement jumping performance, the rate of force development and maximum isometric force. Fifteen moderately-trained young females performed countermovement jumps as well as an isometric leg press test in order to determine the rate of force development and maximum isometric force. Vastus lateralis MFCV was measured with intramuscular microelectrodes at rest on a different occasion. Maximum MFCV was significantly correlated with maximum isometric force (r = 0.66, p < 0.01), nevertheless even closer with the leg press rate of force development at 100 ms, 150 ms, 200 ms, and 250 ms (r = 0.85, r = 0.89, r = 0.91, r = 0.92, respectively, p < 0.01). Similarly, mean MFCV and type II MFCV were better correlated with the rate of force development than with maximum isometric leg press force. Lower, but significant correlations were found between mean MFCV and countermovement jump power (r = 0.65, p < 0.01). These data suggest that muscle fiber conduction velocity is better linked with the rate of force development than with isometric force, perhaps because conduction velocity is higher in the larger and fastest muscle fibers which are recognized to contribute to explosive actions.